Mobilizing the Rights of Homeless EU Citizens in the Netherlands - Dion Kramer (German Law Journal)
This Article explores, from a participatory perspective of an engaged legal scholar, the case of homeless EU citizens in the Netherlands and the mobilization of their rights. By marking them as so-called niet-rechthebbenden (“non-rightholders”), Dutch municipalities have systematically denied homeless EU citizens access to overnight shelters and general homelessness services on equal footing as Dutch citizens. This legal and practical deadlock—a classic case of non-compliance through “law in action”—has most probably led to a denial of rights to EU citizens entitled to shelter as permanent residents, (former) workers, or otherwise legally residing EU citizens. The contribution explores the context and motivations that led a broad coalition of actors—ranging from homelessness organizations, advocacy groups, a public interest litigation organization and legal experts—to join efforts and consider strategic litigation a credible avenue to protect the interests of the most vulnerable under EU law within a national and local context. The case demonstrates, however, how strategic litigation is not considered the most effective or preferred strategy when other avenues for legal mobilization open up.